Experimental and Techno-Economic Analysis of Solar-Geothermal Organic Rankine Cycle Technology for Power Generation in Nepal - Suresh Baral (International Journal of Photoenergy)
The current research study focuses on the feasibility of stand-alone hybrid solar-geothermal organic Rankine cycle (ORC) technology for power generation from hot springs of Bhurung Tatopani, Myagdi, Nepal. For the study, the temperature of the hot spring was measured on the particular site of the heat source of the hot spring. The measured temperature could be used for operating the ORC system. Temperature of hot spring can also further be increased by adopting the solar collector for rising the temperature. This hybrid type of the system can have a high-temperature heat source which could power more energy from ORC technology. There are various types of organic working fluids available on the market, but R134a and R245fa are environmentally friendly and have low global warming potential candidates. The thermodynamic models have been developed for predicting the performance analysis of the system. The input parameter for the model is the temperature which was measured experimentally. The maximum temperature of the hot spring was found to be 69.7°C. Expander power output, thermal efficiency, heat of evaporation, solar collector area, and hybrid solar ORC system power output and efficiency are the outputs from the developed model. From the simulation, it was found that 1 kg/s of working fluid could produce 17.5 kW and 22.5 kW power output for R134a and R245fa, respectively, when the geothermal source temperature was around 70°C. Later when the hot spring was heated with a solar collector, the power output produced were 25 kW and 30 kW for R134a and R245fa, respectively, when the heat source was 99°C. The study also further determines the cost of electricity generation for the system with working fluids R134a and R245fa to be $0.17/kWh and $0.14/kWh, respectively. The levelised cost of the electricity (LCOE) was $0.38/kWh in order to be highly feasible investment. The payback period for such hybrid system was found to have 7.5 years and 10.5 years for R245fa and R134a, respectively.